CURRICULUM IMPLEMENTATION AT MADRASAH ALIYAH SWASTA MAQAMAM MAHMUDA TAKENGON - Maulida (CENDEKIA INDONESIA, 2023)
This study aims to identify and describe the structure of the curriculum and its implementation in Madrasah Aliyah Swasta Maqamam Mahmuda Takengon. This study uses a descriptive method with a qualitative approach. The problems discussed in this study are how the structure of the curriculum and its implementation in Madrasah Aliyah Swasta Maqamam Mahmuda Takengon. The results showed that the curriculum structure at Madrasah Aliyah Swasta Maqamam Mahmuda Takengon implemented a modern pesantren education curriculum, namely the Gontor curriculum and the ministry of religion curriculum which consisted of religious, language and general subjects. The implementation of the curriculum goes well according to a predetermined schedule. Teachers who teach subjects have expertise in their respective fields. All religious teachers are alumni of modern Islamic boarding schools and master the yellow book. Teachers use various strategies in the learning process. Evaluation of learning through written and practical exams.